Promoting gifted students' understanding of everyday life problems - Costu, Fatma (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
The objective of the study is to assess the effectiveness of laboratory activities employing the Predict-Explain-Observe-Discuss-Explain (PEODE) approach in promoting gifted students' interpretation of everyday problems related to fundamental science concepts. This quasi-experimental study involved 54 gifted students enrolled in the Science and Art Center (SAC), divided into an experimental group (EG; n = 28) and a control group (CG; n = 26). While the CG participated in traditional laboratory activities, the EG engaged in PEODE-based. Both groups underwent 16 h of laboratory sessions. An Everyday-life Problem Test (EPT), comprising nine problems, was administered as both a pretest and a post-test to assess gifted students' interpretation of everyday life problems. Pre- and post-test scores from the EPT were analyzed both qualitatively and quantitatively. The results indicated that PEODE-based laboratory contributed to the interpretation of daily life problems among gifted students by diminishing reliance on alternative conceptions compared to traditional laboratory.
Keywords: PEODE-based Laboratory; gifted students; everyday-life problems; alternative conceptions; conceptual change; SCIENCE; OBSERVE; EXPLAIN; PREDICT; CURRICULUM; KNOWLEDGE; EDUCATION; COOKBOOK; Education & Educational Research